A Rare Case of Colonic Sarcoidosis Presenting as a Mass. (10th October 2020) - Sun, Haozhe; Makker, Jasbir; Patel, Harish; Mantri, Nikhitha; Hussain, Ali N.; Abbas, Naeem
Abstract : Introduction . Sarcoidosis is a common multisystem chronic inflammatory disease of an unidentified inciting etiology. The most common initial manifestations of this disease involve the pulmonary system, and involvement of the gastrointestinal tract is rare. Sarcoidosis of the gastrointestinal tract occurs in an oral-anal gradient, with the esophagus and stomach being the most commonly involved sites, while colonic involvement remains extremely rare. Case Presentation . We present a case of a 24-year-old African American man who was evaluated for persistent abdominal pain, chronic diarrhea, and weight loss. Workup for infectious etiologies and celiac disease was unrevealing. An inflammatory mass in the hepatic flexure was found during colonoscopy, and a computed tomography (CT) scan of the abdomen was significant for circumferential thickening of the cecum and ascending colon, along with nodular thickening of the peritoneum without enhancement. Malignancy and inflammatory bowel disease were the initial differentials. A peritoneal biopsy was also performed. Pathology of the colon and peritoneal biopsy was significant for the presence of noncaseating granulomas and confluent granulomatous inflammation. The patient was diagnosed with colonic sarcoidosis, and treatment with corticosteroids was initiated. Symptoms resolved with treatment, and a follow-up colonoscopy five months later showed interval healing. Conclusion . Although rare, colonic sarcoidosis should be considered as one of the differential diagnoses when evaluating a patient with chronic diarrhea and a mass on colonoscopy. Histopathology is the key to diagnosis as it distinguishes malignancy from sarcoidosis. Corticosteroids remain as an option for treating colonic sarcoidosis.